Noncompaction of left ventricle - a rare cardiomyopathy - Thakkar, Parth K.; Bhatt, Mahesh; Chawla, Sheela Bharani; Desai, Hitesh (International Journal of Contemporary Pediatrics, 2021)
Non-compaction of left ventricular (NCLV) is a rare cardiomyopathy of unknown origin characterized by prominent ventricular trabeculations and deep intertrabecular sinusoids, in communication with the left ventricular cavity. The NCLV results due to failure of compaction during foetal development. In this study, five children were diagnosed with NCLV out of 135 cases of cardiomyopathy and the youngest case was diagnosed at 27th day of life. Congestive cardiac failure presenting as tachycardia and tachypnea were common clinical manifestations. Early detection of NCLV helps patients to get timely treatment. NCLV should be considered as one of the differential diagnosis amongst cases of cardiomyopathy.